The business of fancydancing [videorecording (DVD)] - Adams, Evan; Tagaban, Gene; St. John, Michelle (Milestone Film & Video, 2026)
Since their high school graduation, former Spokane Reservation best friends Seymour and Aristotle have taken different paths. Both ventured off to college in Seattle, but while Seymour embraced the opportunities of the white world, Aristotle returned home embittered. Sixteen years later, they are brought together following the sudden death of an old childhood buddy. Seymour, now an openly gay poet and unofficial spokesman for Native Americans, is met with resentment on "the rez." At the wake, tensions are heightened, and Aristotle's long festering bitterness is dangerously exposed.